2024
DOI: 10.1167/iovs.65.4.31
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus Hypoxia Adaptation Is Critical for the Establishment of Fungal Keratitis

Jorge D. Lightfoot,
Emily M. Adams,
Manali M. Kamath
et al.

Abstract: Purpose The poor visual outcomes associated with fungal keratitis (FK) underscore a need to identify fungal pathways that can serve as novel antifungal targets. In this report, we investigated whether hypoxia develops in the FK cornea and, by extension, if fungal hypoxia adaptation is essential for virulence in this setting. Methods C57BL/6J mice were inoculated with Aspergillus fumigatus and Fusarium solani var. petroliphilum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…They also observed that during the progression of the infection, as the corneal edema progressed, the degree of hypoxia increased, and the endothelium decreased. Later, in the following stages, the accumulation of fungal metabolites together with leukocyte ROS/cytokines caused further loss of endothelial integrity and subsequent entry of fluid from the anterior chamber [66].…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…They also observed that during the progression of the infection, as the corneal edema progressed, the degree of hypoxia increased, and the endothelium decreased. Later, in the following stages, the accumulation of fungal metabolites together with leukocyte ROS/cytokines caused further loss of endothelial integrity and subsequent entry of fluid from the anterior chamber [66].…”
Section: Immune Mechanismsmentioning
confidence: 99%